Pulmonary and Systemic Skeletal Muscle Embolism in a Beaked Whale with a Massive Trauma of Unknown Aetiology - Eva Sierra; Tania Ramírez; Yara Bernaldo de Quirós; Marina Arregui; Blanca Mompeó; Miguel A. Rivero; Antonio Fernández (Animals, 2022)
An adult female Sowerby’s beaked whale was found floating dead in Hermigua (La Gomera, Canary Islands, Spain) on 7 December 2016. Severe traumas of unknown aetiology were attributed, and the gross and microscopic findings are consistent with catastrophic trauma as a cause of death. Rib fractures affected the intercostals, transverse thoracis skeletal muscles, and thoracic rete mirabile. Degenerated muscle fibres were extruded to flow into vascular and lymphatic vessels travelling to several anatomic locations into the thoracic cavity, including the lungs, where they occluded the small lumen of pulmonary microvasculature. A pulmonary and systemic skeletal muscle embolism was diagnosed, constituting the first description of this kind of embolism in an animal. The only previous description has been reported in a woman after peritoneal dialysis. Skeletal pulmonary embolism should be considered a valuable diagnostic for different types of trauma in vivo in wild animals. This is especially valuable when working with decomposed carcasses, as in those cases, it is not always feasible to assess other traumatic evidence.